Multilayer structure electro-catalysis anode with long service life and preparation method of multilayer structure electro-catalysis anode
By designing a multi-layer structure electrocatalytic anode, including a conductive base layer, an electroplating intermediate layer and a precious metal oxide surface layer, the problem of dissolution and shedding of the active components of the precious metal is solved, achieving a longer service life and lower cost, while improving the conductivity and binding force of the anode.
Patent Information
- Application Number
- CN202411650175.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-03-28
AI Technical Summary
During use, traditional electrolytic copper foil anode is easily dissolved and shed due to the reaction of precious metal active components and organic additives, resulting in the failure of the anode, shortened service life, and high cost.
The multi-layer structure electrocatalytic anode is adopted, including insoluble metal substrates, conductive base layers (mainly IrO2-Ta2O5), electroplating intermediate layers (mainly β-PbO2) and precious metal oxide surface layers (mainly IrO2 and PbO2). Through reasonable coating structure and process design, the binding force and conductivity of the anode are improved.
It extends the service life of the anode, reduces costs, improves the conductivity and binding force of the electrode, effectively prevents the passivation of the substrate, and improves the overall performance of the electrocatalytic anode.
Smart Images

Figure CN119710833A_ABST
Abstract
Description
Technical Field
[0001] The present invention mainly relates to the technical field of electrocatalytic anodes, and specifically relates to a multi-layer electrocatalytic anode with a long working life and a preparation method thereof. Background Art
[0002] With the rapid development of new energy, electronic information and other industries, the quality requirements for electrolytic copper foil are constantly increasing. Taking new energy lithium battery copper foil as an example, lithium battery copper foil as the negative electrode current collector needs to have good conductivity, flexibility and oxidation resistance to ensure the charging and discharging performance and safety of the battery. Therefore, it is necessary to add a variety of organic additives to the electrolyte, including brighteners, leveling agents, and positioning agents. During the electrolysis process, the precious metal oxides on the surface of the traditional anode are easily complexed with organic additives, or the precious metal active components react with the reducing organic additives to undergo redox reactions, thereby causing the dissolution and shedding of the precious metal active components, thereby accelerating the failure of the anode and reducing the service life of the anode.
[0003] As one of the essential equipment components for producing copper foil, electrolytic copper foil anode directly affects the product quality of copper foil. Traditional electrolytic copper foil anodes are mostly iridium-tantalum-coated titanium anodes with high iridium content, with iridium content > 24g / m 2 , the cost of raw materials is very high, and the active components of the coating are exposed to the electrolyte for a long time, which is easy to be deactivated and dissolved during the working process, making the electroplating reaction uneven, and finally leading to the failure of the anode (the failure of insoluble anodes is mainly due to the following reasons: poor design or process preparation leads to the dissolution of active components; poor bonding leads to the shedding of active components and cracking of coatings; passivation failure of the substrate). As the use environment of electrolytic copper foil anodes becomes increasingly severe and the price of precious metal raw materials increases, it is more important to develop lower-cost and high-performance anodes while ensuring the service life of copper foil anodes. Summary of the invention
[0004] The technical solution of the present invention aims at the technical problem that the existing technical solutions are too single, and provides a solution that is significantly different from the existing technologies. It mainly provides a multi-layer structure electrocatalytic anode with a long working life and a preparation method thereof, so as to solve the technical problem raised in the above background technology of developing lower cost and high performance anode materials while ensuring the service life of the copper foil anode.
[0005] The technical solution adopted by the present invention to solve the above technical problems is: A multi-layer electrocatalytic anode with a long working life comprises an insoluble metal substrate, a conductive bottom layer, an electroplated middle layer, and a noble metal oxide surface layer arranged in sequence; the main component of the conductive bottom layer is IrO2-Ta2O5; the main component of the electroplated middle layer is β-PbO2; the main components of the noble metal oxide surface layer are IrO2 and PbO2, and the iridium content of the noble metal oxide surface layer is 6-10 g / m 2 , the lead content is 12~20g / m 2 .
[0006] Specifically, the thickness of the conductive bottom layer is 0.3 to 1 μm; And / or, the thickness of the electroplated intermediate layer is 20 to 50 μm; And / or, the thickness of the precious metal surface layer is 3 to 6 μm.
[0007] Specifically, the insoluble metal substrate is titanium or titanium alloy, and the surface has been pre-treated by sandblasting and etching.
[0008] The present invention also provides a method for preparing a multilayer electrocatalytic anode with a long working life, comprising the following steps: S1. Pre-treat the insoluble metal substrate, clean it and dry it for later use; S2, coating the substrate surface treated in S1 with a bottom solution, drying it, and sintering it at high temperature; repeating the coating-drying-sintering process 2 to 4 times; the amount of liquid coated each time is the same, and the molar ratio of iridium element to tantalum element in the bottom solution is 1:1 to 3:2; S3, placing the material treated by S2 in a lead-containing electroplating solution to electro-deposit a β-PbO2 intermediate layer; the composition of the electroplating solution is: Pb(NO3)2 200-400g / L, HNO3 20-40g / L, polyethylene glycol 2-6g / L, polyvinyl pyrrolidone 0.5-2g / L; S4. Apply a surface solution to the surface of the material treated in S3, then dry and sinter at high temperature; repeat the coating-drying-sintering process 3 to 10 times to obtain a multi-layer electrocatalytic anode with a long working life; the amount of liquid applied each time is consistent, and the molar ratio of iridium to lead in the solution is 1:4 to 1:2.
[0009] Furthermore, in step S1, the pretreatment is: machining, degreasing, sandblasting, and acid etching the substrate in sequence.
[0010] Furthermore, the acid used in the acid etching is a mixed acid of hydrochloric acid and oxalic acid, wherein the concentration of hydrochloric acid is 15% to 30%, and the concentration of oxalic acid is 0 to 10%; the state of the mixed acid is a boiling state, and the etching time is 10 to 50 minutes.
[0011] Further, in step S2, the drying temperature is 70-100°C each time, and the drying time is 10-20 minutes each time; And / or, the sintering temperature is 480-510° C. each time, and the sintering time is 25-45 min each time.
[0012] Further, in step S3, the bath temperature is 30-60°C; and / or, the current density is 0.05 to 0.2 A / m 2 The power-on time is 1 to 3 hours.
[0013] Further, in step S4, the drying temperature is 70-100° C. each time, and the drying time is 10-20 min each time; And / or, the sintering temperature is 480-510° C. each time, and the sintering time is 45-60 min each time.
[0014] Further, in step S2, the bottom solution is a mixed solution including H2IrCl6·6H2O and TaCl5; And / or, in step S4, the surface solution is a mixed solution including H2IrCl6·6H2O and Pb(NO3)2.
[0015] Compared with the prior art, the present invention has the following beneficial effects: The multilayer structure electrocatalytic anode provided by the present invention is provided with a conductive bottom layer between the substrate and the electroplating middle layer, and the main component of the conductive bottom layer is IrO2-Ta2O5; compared with the currently common single-layer or double-layer coated titanium-based Ir-Ta oxide anode and lead dioxide anode, iridium oxide has strong conductivity but poor compactness; tantalum oxide has a very dense structure and good bonding with the substrate and the electroplating middle layer, which can inhibit the oxidation of the titanium substrate during the preparation process and prevent the substrate from being passivated during the operation of the end anode, but has low conductivity. The conductive bottom layer adopts IrO2-Ta2O5, and iridium oxide and tantalum oxide complement each other in advantages and disadvantages to form a highly conductive and dense iridium tantalum oxide bottom layer, which can prevent the substrate titanium from being passivated during the electroplating middle layer; and can improve the bonding strength of the plating layer and improve its conductivity.
[0016] The main component of the electroplating middle layer of the multi-layer structure electrocatalytic anode provided by the present invention is β-PbO2, which has good electroplating ability, excellent electroplating morphology and structure, low electroplating cost, and lead dioxide itself has a certain electrocatalytic ability, and can also provide a certain catalytic activity after the surface layer of the precious metal oxide fails. β-PbO2, as a product of the electroplating process provided by the present invention, has a dense structure, good bonding with the conductive bottom layer and the surface layer of the precious metal oxide; good insolubility; strong conductivity, can provide higher electrical conductivity; easy to produce and prepare.
[0017] In the electrode material, the function of the intermediate layer is mainly to prevent the substrate from being passivated, and generally a dense material is required. The intermediate layer commonly used in the market is generally prepared by a thermal decomposition process. Although its structure is dense, its conductivity is poor, resulting in its thickness being maintained below 5 μm, and being too thick will also lead to the influence of poor bonding, and being too thin will reduce its ability to inhibit the passivation of the substrate. In the present invention, since it uses an electroplating process, while having the function of a conventional intermediate layer, the thickness can be plated thicker to further enhance its ability to prevent the passivation of the substrate. Within the thickness range provided by the present invention, combined with the pretreatment of the substrate to form a rough surface and the provision of a conductive bottom layer, it will not have the disadvantages of reduced adhesion and poor conductivity.
[0018] When preparing the electroplating intermediate layer in the preparation method provided by the present invention, polyethylene glycol is added as an additive in the electroplating solution. During the electroplating process, the molecular chain of polyethylene glycol can fill the microscopic unevenness of the electrode surface, so that the metal ions in the plating solution can be more evenly distributed during deposition, and preferentially adsorbed on the protruding parts, to a certain extent, hindering the excessive deposition of metals in these parts; polyethylene glycol can also interact with metal ions or other additives in the electroplating solution to affect the deposition mode of the metal. That is, it helps to increase the deposition rate of lead ions and optimize their crystal morphology. The densely structured lead dioxide can effectively prevent the diffusion of oxygen and the erosion of the substrate during the working process of the electrode, thereby helping to avoid the passivation failure of the substrate.
[0019] When preparing the electroplating intermediate layer in the preparation method provided by the present invention, polyvinyl pyrrolidone is also added to the electroplating solution as an additive. On the one hand, it acts as a dispersant. The pyrrolidone ring structure in the PVP molecule can interact with metal ions. Its molecular chain prevents metal ions or metal particles from approaching each other through the steric hindrance effect, so that they are evenly dispersed in the electroplating solution, thereby promoting uniform electroplating; on the other hand, PVP can reduce the surface tension between the electroplating solution and the surface of the plated part, enhance the wettability of the electroplating solution to the surface of the plated part, and prevent uneven electroplating or defects such as pinholes. Comprehensive polyethylene glycol and polyvinyl pyrrolidone as additives can play a leveling role (preventing transitional product of a single area), a dispersing role (making electroplating uniform), a coordination role (multiple additives cooperate well with each other), a wetting role (reducing surface tension and preventing local electroplating from not being applied), etc.
[0020] The main components of the surface layer of the precious metal oxide of the present invention are IrO2 and PbO2. The oxygen evolution potential of iridium oxide is low, which helps to reduce the oxygen evolution potential of the anode as a whole and reduce the electricity cost in the process of electrolytic copper foil. Lead dioxide with high oxygen evolution potential can react with the reducing additive in the electrolytic copper foil electrolyte to prevent the complexation and redox reaction between it and the precious metal active component, and inhibit the dissolution and consumption of the precious metal active component. In addition, the iridium content in the surface layer of the precious metal oxide is set to 6-10 g / m2 , the lead content is 12~20g / m 2 If the iridium content is too high, the cost will increase significantly and it will be difficult to ensure the density of the coating. If it is too low, the original design intention will be lost, resulting in insufficient ability to cope with complex working conditions. In the present invention, the difference between the two contents is not very large, and the thermal decomposition method is adopted to make the two uniformly distributed in the coating structure, so that the surface layer of the precious metal oxide can simultaneously reduce the electricity cost and inhibit the dissolution and consumption of the precious metal active components.
[0021] In summary, the present invention can solve the problem of active component dissolution caused by poor design or process preparation by optimizing the structure and process of the multilayer electrocatalytic anode; and improve the bonding strength of the coating to solve the problem of active component shedding and coating cracking caused by poor bonding strength; and can also effectively prevent the passivation of the substrate. The present invention has good bonding strength, the active component is not easy to dissolve, and the substrate can be prevented from passivation, which makes the electrocatalytic anode have a longer service life. In addition, the electrocatalytic anode provided by the present invention also has the advantages of lower cost and high performance.
[0022] The present invention will be explained in detail below with reference to the accompanying drawings and specific embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a SEM surface morphology image of the electrocatalytic anode in Example 1 of the present invention. DETAILED DESCRIPTION
[0024] To facilitate understanding of the present invention, the present invention will be described more comprehensively below with reference to the relevant drawings. Several embodiments of the present invention are given in the drawings, but the present invention can be implemented in different forms and is not limited to the embodiments described in the text. On the contrary, these embodiments are provided to make the content disclosed in the present invention more thorough and comprehensive.
[0025] Embodiment 1: This embodiment provides a multilayer electrocatalytic anode with a long service life, comprising: Insoluble metal substrate, titanium or titanium alloy; The conductive bottom layer mainly consists of IrO2-Ta2O5, and the thickness of the conductive bottom layer is 0.3 to 1 μm. Iridium oxide and tantalum oxide are insoluble in most acid, alkali and salt environments, which is one of the necessary conditions for insoluble anodes; iridium oxide has strong conductivity, and the same iridium element as that in the surface layer can simplify the process preparation principle; the structure of tantalum oxide is very dense, and it has good bonding with the substrate and the electroplating intermediate layer, which can inhibit the oxidation of the titanium substrate during the preparation process and prevent the substrate from being passivated during the operation of the end anode. However, the conductivity of tantalum oxide is low, and the density of iridium oxide is poor, so this structure is adopted to make the two oxides complement each other. If the conductive bottom layer is too thick, the bonding strength of the coating will be poor; if it is too thin, there will be uncovered areas on the surface of the substrate.
[0026] The electroplating intermediate layer, whose main component is β-PbO2, has a thickness of about 40 μm; the function of the electroplating intermediate layer is mainly to prevent the substrate from being passivated, and generally requires a dense material, and the commonly used intermediate layer on the market is generally prepared by a thermal decomposition process, and although its structure is dense, its conductivity is poor. The β-PbO2 in the present invention is a product of the electroplating process, and its structure is dense, insoluble, and highly conductive, and it also has certain catalytic activity; because it uses the electroplating process, while having the function of a conventional intermediate layer, the thickness can be plated thicker, further strengthening its ability to prevent the substrate from being passivated. Within the thickness range of the present invention, there will be no disadvantages such as reduced adhesion and poor conductivity.
[0027] Precious metal oxide surface layer; the main components are IrO2, PbO2, iridium oxide and lead oxide, both of which have catalytic activity, but their oxygen evolution potential, solubility in different environments and costs are different. Iridium oxide and lead oxide are catalytically active components, and their different catalytic properties can cope with more complex end-use environments. Such a design can make the anode have a longer working life. The selection of lead oxide also takes into account its stability with the intermediate layer (the same element). The iridium content in the precious metal oxide surface layer is 8g / m 2 , the lead content is 16g / m 2 This content is based on the following considerations: iridium is a precious metal and is expensive. Too high a content will significantly increase the cost and cause waste; too low a content will result in insufficient catalytic activity. The thickness of the precious metal surface layer is 3 to 6 μm. Too thick a thickness will result in poor bonding and easy detachment, while too thin a thickness means that the catalyst dosage is too low and the catalytic capacity is insufficient.
[0028] Elements with good compatibility and stability are selected between different coating layers. If different elements are selected, other factors need to be considered. For example, the coating may crack and have poor bonding strength due to the large difference in thermal expansion coefficients between different layers. The present invention can avoid such problems by selecting the same elements as much as possible.
[0029] The specific preparation process of the above electrocatalytic anode is as follows: S1. Matrix pretreatment: Select an industrial titanium plate with a thickness of 6 mm (made of TA1), cut it to a size of 200*200*6 mm by machining, remove oil and sandblast it, then etch it in a mixture of boiling 20% hydrochloric acid and 5% oxalic acid for 25 minutes, rinse it with pure water, dry it and set it aside for use; S2, preparation of conductive bottom layer: take 0.5 ml of mixed bottom layer solution of H2IrCl6·6H2O and TaCl5, and evenly coat it on the surface of the pre-treated titanium plate, the molar ratio of H2IrCl6·6H2O and TaCl5 is 1:1; dry it in an oven at 80 ℃ for 15 min, place it in a sintering furnace at 500 ℃ for 30 min, repeat the coating-drying-sintering process 3 times and then set it aside; S3, preparation of electroplating middle layer: prepare electroplating solution, the composition of which is: Pb(NO3)2300g / L, HNO3 30g / L, polyethylene glycol 3g / L, polyvinyl pyrrolidone 1g / L; the bath temperature is 50℃. Place the anode with the prepared bottom layer in the above electroplating solution, and set the current density to 0.1A / cm 2 , electroplating for 1.5 h, and electrodeposition of β-PbO2; S4. Preparation of precious metal oxide surface layer: Take 0.6 ml of the surface solution of H2IrCl6·6H2O and Pb(NO3)2, with the molar ratio of H2IrCl6·6H2O and Pb(NO3)2 being 1:2; evenly coat it on the surface of the anode after electrodeposition, dry it in an oven at 80°C for 15 min, and sinter it in a sintering furnace at 500°C for 50 min. Repeat the coating-drying-sintering process 8 times to obtain a multi-layered electrocatalytic anode.
[0030] Its surface SEM morphology is shown in Figure 1 As shown, large-sized lead oxide grains are dispersed on the surface, and small-sized iridium oxide grains exist mainly in the form of solid solution. This distribution ensures the uniformity of the local real current during the operation of the anode, thereby inhibiting the dissolution of the active components of iridium oxide, which is beneficial to increasing the working life of the anode.
[0031] Embodiment 2: This embodiment differs from Embodiment 1 in that: When the precious metal oxide surface layer is prepared, the coating-drying-sintering process is repeated four times to obtain a multi-layered electrocatalytic anode.
[0032] The rest is the same as the first embodiment.
[0033] Embodiment 3: This embodiment differs from Embodiment 1 in that: The thickness of the electroplated intermediate layer is about 50 μm. When preparing the electroplated intermediate layer, the current density is set to 0.2 A / cm 2 , electroplating for 3h.
[0034] The rest is the same as the first embodiment.
[0035] Embodiment 4: This embodiment differs from Embodiment 1 in that: The iridium content in the surface layer of the noble metal oxide is 10 g / m 2 , the lead content is 12g / m 2 .
[0036] In the substrate pretreatment, after sandblasting, it was etched in a mixture of boiling 15% hydrochloric acid and 10% oxalic acid for 50 minutes.
[0037] When preparing the conductive bottom layer, the molar ratio of H2IrCl6·6H2O and TaCl5 in the bottom layer solution was 1.3:1; it was dried in an oven at a temperature of 70°C for 20 min and sintered in a sintering furnace at a temperature of 510°C for 25 min; the coating-drying-sintering process was repeated 4 times.
[0038] When preparing the electroplating intermediate layer, the thickness of the electroplating intermediate layer is about 20 μm; the composition of the electroplating solution is: Pb(NO3) 2400 g / L, HNO3 40 g / L, polyethylene glycol 6 g / L, polyvinyl pyrrolidone 2 g / L; the current density is set to 0.05 A / cm 2 , electroplating for 1h; the bath temperature is 30℃.
[0039] When preparing the precious metal oxide surface layer, the molar ratio of H2IrCl6·6H2O and Pb(NO3)2 in the surface solution is 1:3; it is dried in an oven at a temperature of 70°C for 20 min and sintered in a sintering furnace at a temperature of 510°C for 45 min; after repeating the coating-drying-sintering process 10 times, a multi-layered electrocatalytic anode is obtained.
[0040] The rest is the same as the first embodiment.
[0041] Embodiment 5: This embodiment differs from Embodiment 1 in that: The iridium content in the surface layer of the noble metal oxide is 6 g / m 2 , the lead content is 20g / m 2 .
[0042] In the substrate pretreatment, after sandblasting, it was etched in a mixed acid of boiling 30% hydrochloric acid for 10 minutes.
[0043] When preparing the conductive bottom layer, the molar ratio of H2IrCl6·6H2O and TaCl5 in the bottom layer solution is 3:2; it is dried in an oven at a temperature of 100°C for 10 min and sintered in a sintering furnace at a temperature of 480°C for 45 min; the coating-drying-sintering process is repeated twice.
[0044] When preparing the electroplating intermediate layer, the electroplating solution composition is: Pb(NO3)2200g / L, HNO3 20g / L, polyethylene glycol 2g / L, polyvinyl pyrrolidone 0.5g / L; the bath temperature is 60°C.
[0045] When preparing the surface layer of the precious metal oxide, the molar ratio of H2IrCl6·6H2O and Pb(NO3)2 in the surface solution is 1:4; it is dried in an oven at a temperature of 100°C for 10 min and sintered in a sintering furnace at a temperature of 480°C for 60 min; after repeating the coating-drying-sintering process three times, a multi-layered electrocatalytic anode is obtained.
[0046] The rest is the same as the first embodiment.
[0047] Comparative Example 1: A common double-layer titanium-based Ir-Ta oxide titanium anode in the industry, the preparation method of which is as follows: Substrate pretreatment: select an industrial titanium plate with a thickness of 6 mm (made of TA1), machine cut it to a size of 200*200*6 mm, remove oil and sandblast it, then etch it in 25%wt HCl at above 95°C for 20 minutes, rinse it with pure water, dry it and set it aside for use; Preparation of electroplating intermediate layer: Take 0.5 ml of the mixed intermediate layer solution of TiCl4 and TaCl5, evenly coat it on the surface of the pre-treated titanium plate, dry it in an oven at 80 °C for 15 min, sinter it in a sintering furnace at 530 °C for 50 min, repeat the coating-drying-sintering process 5 times and then set it aside; Preparation of precious metal oxide catalyst layer: Take 0.6 ml of the catalyst layer solution of H2IrCl6·6H2O and TaCl5, evenly coat it on the surface of the titanium plate prepared with the electroplated intermediate layer, dry it in an oven at 80°C for 15 min, and sinter it in a sintering furnace at 520°C for 30 min. After repeating the coating-drying-sintering process 24 times, a coated titanium anode with a structure of Ti / TiO2+Ta2O5 / IrO2+Ta2O5 was finally obtained.
[0048] Comparative Example 2: A common lead dioxide titanium anode in the industry, whose preparation method is different from the preparation method in Example 1 in that a conductive bottom layer and a precious metal oxide surface layer are not prepared on its surface, that is, β-PbO2 is electrodeposited on the substrate.
[0049] Comparative Example 3: The difference from Example 1 is that: No electroplating intermediate layer preparation is performed.
[0050] The rest is the same as the first embodiment.
[0051] Comparative Example 4: The difference between this embodiment and the first embodiment is that: When preparing the electroplating intermediate layer, the composition of the electroplating solution is: Pb(NO3) 2400g / L, HNO3 40g / L.
[0052] The rest is the same as the first embodiment.
[0053] The electrodes prepared in Examples 1 to 5 and Comparative Examples 1 to 4 were subjected to electrode potential test, accelerated life test and coating adhesion test.
[0054] 1) The electrode potential test conditions are as follows: Current density: 50 A / m 2 ; Temperature: 25 ℃; Electrolyte: 150 g / L sulfuric acid solution; Reference electrode: mercurous sulfate; Cathode: Zr; Pole distance: 1 cm.
[0055] 2) Accelerated life test conditions are as follows: Current density: 5A / cm 2 ; Electrolysis temperature: 60 ℃; Electrolyte: 150 g / L sulfuric acid solution; Cathode: Ti; Pole distance: 1 cm.
[0056] The accelerated life test ends when the electrolysis voltage rises by 1 V compared to the initial voltage.
[0057] 3) The film adhesion test is carried out using an automatic scratch tester, and the test conditions are as follows: Detection mode: acoustic emission; Loading load: 100 N; Loading mode: unidirectional continuous loading; Scratch length: 6 mm; Loading rate: 60 N / min.
[0058] The bonding strength test result is the critical load value at which the coating begins to fail.
[0059] The test results of the above three parameters are shown in Table 1.
[0060] Table 1 Comparison of performance tests of embodiments and comparative examples Sample No. Compared with Example 1, the preparation process changes Electrode potential (V) Lifespan (h) Coating bonding strength (N) Embodiment 1 / 0.94 1300 60 Embodiment 2 Different number of surface coatings 0.96 1180 64 Embodiment 3 The electrical parameters of the middle layer are different 0.97 1100 55 Embodiment 4 The preparation process parameters of each layer are different 0.95 1270 56 Embodiment 5 The preparation process parameters of each layer are different 0.96 1210 61 Comparative Example 1 Traditional Iridium Tantalum Titanium Anode 0.93 1060 58 Comparative Example 2 No conductive bottom layer, no precious metal oxide surface layer 1.36 640 54 Comparative Example 3 Electroless intermediate layer 0.93 880 57 Comparative Example 4 Intermediate layer plating solution without additives 0.97 980 51 Comparing Examples 1 to 5 with Comparative Example 1, it can be seen that the multi-layer electrocatalytic anode prepared by the present invention can achieve a service life that is superior to that of the traditional iridium-tantalum coated titanium anode under the premise of preparing the electroplated intermediate layer with a suitable preparation process.
[0061] By comparing Examples 1 to 5 with Comparative Example 2, it can be seen that the present invention can effectively improve the adhesion and service life of the coating and greatly reduce its surface oxygen evolution potential by preparing a conductive bottom layer on the surface of the anode and preparing a precious metal oxide surface layer on the surface of the electroplated lead dioxide layer.
[0062] Comparing Examples 1 to 5 with Comparative Example 3, it can be seen that the electroplated intermediate layer in the electrocatalytic anode is one of the keys to prolonging the service life of the anode.
[0063] Comparing Examples 1 to 5 with Comparative Example 4, it can be seen that adding additives to the electroplating solution for electroplating the intermediate layer can greatly improve the coating bonding strength of the anode and extend the service life of the anode.
[0064] Comparing Example 1 with Examples 2 and 3, it can be seen that suitable preparation parameters can provide a longer service life.
[0065] In summary, the present invention provides a multilayer electrocatalytic anode with a long working life. By designing a reasonable coating structure and solution formula, the working life of the electrode can be effectively improved, and it has broad application prospects in the field of electrolytic copper foil surface treatment.
[0066] The above is an exemplary description of the present invention in combination with the accompanying drawings. It is obvious that the specific implementation of the present invention is not limited to the above-mentioned method. As long as such non-substantial improvements are made by adopting the method concept and technical solution of the present invention, or the concept and technical solution of the present invention are directly applied to other occasions without improvement, they are all within the protection scope of the present invention.
Claims
1. A multi-layer electrocatalytic anode with a long service life, characterized in that: The invention comprises an insoluble metal substrate, a conductive bottom layer, an electroplated middle layer, and a noble metal oxide surface layer which are arranged in sequence; the main component of the conductive bottom layer is IrO2-Ta2O5; the main component of the electroplated middle layer is β-PbO2; the main components of the noble metal oxide surface layer are IrO2 and PbO2, and the iridium content in the noble metal oxide surface layer is 6-10 g / m 2 , the lead content is 12~20g / m 2 .
2. The multi-layer electrocatalytic anode with a long service life according to claim 1, characterized in that: The thickness of the conductive bottom layer is 0.3 to 1 μm; And / or, the thickness of the electroplated intermediate layer is 20 to 50 μm; And / or, the thickness of the precious metal surface layer is 3 to 6 μm.
3. The multi-layer electrocatalytic anode with a long service life according to claim 1, characterized in that: The insoluble metal substrate is titanium or titanium alloy, and the surface is pre-treated by sandblasting and etching.
4. A method for preparing a multilayer electrocatalytic anode with a long working life according to any one of claims 1 to 3, characterized in that: The steps include: S1. Pre-treat the insoluble metal substrate, clean it and dry it for later use; S2, coating the bottom solution on the surface of the substrate treated in S1, and then drying and sintering at high temperature; Repeat the coating-drying-sintering process 2 to 4 times; the amount of liquid coated each time is the same, and the molar ratio of iridium element to tantalum element in the bottom solution is 1:1 to 3:2; S3, placing the material treated by S2 in a lead-containing electroplating solution to electro-deposit a β-PbO2 intermediate layer; the composition of the electroplating solution is: Pb(NO3)2 200-400g / L, HNO3 20-40g / L, polyethylene glycol 2-6g / L, polyvinyl pyrrolidone 0.5-2g / L; S4, coating the surface solution on the surface of the material treated in S3, then drying and sintering at high temperature; Repeat the coating-drying-sintering process 3 to 10 times to obtain a multilayer electrocatalytic anode with a long working life; the amount of liquid coated each time is consistent, and the molar ratio of iridium element to lead element in the solution is 1:4 to 1:
2.
5. The method for preparing a multilayer electrocatalytic anode with a long working life according to claim 4, characterized in that: In step S1, the pretreatment is: machining, degreasing, sandblasting, and acid etching the substrate in sequence.
6. The method for preparing a multilayer electrocatalytic anode with a long working life according to claim 5, characterized in that: The acid used in the acid etching is a mixed acid of hydrochloric acid and oxalic acid, wherein the concentration of the hydrochloric acid is 15% to 30%, and the concentration of the oxalic acid is 0 to 10%; the state of the mixed acid is a boiling state, and the etching time is 10 to 50 minutes.
7. The method for preparing a multilayer electrocatalytic anode with a long working life according to claim 4, characterized in that: In step S2, the drying temperature is 70-100°C each time, and the drying time is 10-20 minutes each time; And / or, the sintering temperature is 480-510° C. each time, and the sintering time is 25-45 min each time.
8. The method for preparing a multilayer electrocatalytic anode with a long working life according to claim 4, characterized in that: In step S3, the bath temperature is 30-60°C; and / or, the current density is 0.05 to 0.2 A / m 2 The power-on time is 1 to 3 hours.
9. The method for preparing a multilayer electrocatalytic anode with a long working life according to claim 4, characterized in that: In step S4, the drying temperature is 70-100° C. and the drying time is 10-20 min. And / or, the sintering temperature is 480-510° C. each time, and the sintering time is 45-60 min each time.
10. The method for preparing a multilayer electrocatalytic anode with a long working life according to claim 4, characterized in that: In step S2, the bottom solution is a mixed solution including H2IrCl6·6H2O and TaCl5; And / or, in step S4, the surface solution is a mixed solution including H2IrCl6·6H2O and Pb(NO3)2.
Citation Information
Patent Citations
A composite lead dioxide electrode plate and its manufacturing method
CN102280626A
Titanium anode suitable for organic additive application system and manufacturing method thereof
CN117646270A
Anodes with extended service life and methods for their manufacturing
EP0538955A1
Indium-doped titanium-based lead dioxide electrode, and manufacturing method thereof and application of same
WO2018023912A1
Cited By
PbO-M / copper hydrogen storage catalyst, preparation method thereof and application of PbO-M / copper hydrogen storage catalyst in electro-synthesis of sodium borohydride
CN120738700A